Gaming the future: a practitioner's view. Issue 2 (28th June 2019) - Aguilar-Millan, Stephen John
Abstract : Purpose: The purpose of this paper is to examine the links between the practice of gaming and the practice of futures. Design/methodology/approach: The approach is to isolate the steps involved in game design and compare them with the steps involved in designing a futures project. Findings: The findings are that there are significant commonalities between the two processes. Research limitations/implications: The implications are that gaming should be more widely used in the practice of futures. Originality/value: The value of the piece lies in alerting practitioners to the option of using gaming as a futures tool.